What the eyes don't see: a story of crisis, resistance, and hope in an American city (Random House Large Print, One World, an imprint of Random House, Random House Publishing Group, Books on Tape, Random House Audio, an imprint of the Penguin Random House Audio Publishing Group, 2018)
"The dramatic story of the signature environmental disaster of our time and an inspiring tale of scientific resistance by a relentless physician who stood up to power. Flint was already a troubled city in 2014 when the state of Michigan--in the name of austerity--shifted the source of its water supply from Lake Huron to the Flint River. Soon after, citizens began complaining about the water that flowed from their taps--but officials rebuffed them, insisting that the water was fine. Dr. Mona Hanna-Attisha, a pediatrician at the city's public hospital, took state officials at their word and encouraged the parents and children in her care to continue drinking the water--after all, it was American tap water, blessed with the state's seal of approval. But a conversation at a cookout with an old friend, leaked documents from a rogue environmental inspector, and the activism of a concerned mother raised red flags about lead--a neurotoxin whose irreversible effects fall most heavily on children. Even as circumstantial evidence mounted and protests grew, Dr. Mona knew that the only thing that could stop the lead poisoning was undeniable proof--and that to get it, she'd have to enter the fight of her life. What the Eyes Don't See is the inspiring story of how Dr. Mona--accompanied by an idiosyncratic team of researchers, parents, friends, and community leaders--proved that Flint's kids were exposed to lead and then fought her own government and a brutal backlash to expose that truth to the world. Paced like a scientific thriller, this book shows how misguided austerity policies, the withdrawal of democratic government, and callous bureaucratic indifference placed an entire city at risk. And at the center of the story is Dr. Mona herself--an immigrant, doctor, scientist, and mother whose family's activist roots inspired her pursuit of justice. What the Eyes Don't See is a riveting, beautifully rendered account of a shameful disaster that became a tale of hope, the story of a city on the ropes that came together to fight for justice, self-determination, and the right to build a better world for their--and all of our--children."--Dust jacket.
How I got my name , What the eyes don't see , The barbecue , The valedictorian , Haji , Red flags , First encounter , Miasma , No response , Sit down , Jenny + the data , Public health enemy #1 , What field are you on? , The man in the panda tie , Environmental injustice , Poisoned by policy , Shortwave radio crackling , Meeting the Mayor , Aeb , The press conference , Splice and dice , Numbers war , Demonstration of proof , All the things we found out later , Fire ant , Truth and reconciliation , Prescription for hope , Haji and the birds.

What did we use before toilet paper?: 200 curious questions & intriguing answers (Fascinating Bathroom Readers, ,, 2010)
"Presents a collection of two hundred trivia questions and answers covering a wide range of topics."--
Why is the sky blue? -- Why are moths attracted to lights? -- Can the Great Wall of China be seen from space? -- Why were neckties invented? -- What causes jet lag and how can it be prevented and cured? -- Why do we yawn and why is it contagious? -- What is a blue moon? -- Does water travel down the drain in different directions in the Northern and Southern Hemispheres? -- Do you get wetter when walking in the rain than you do when running? -- Is one dog year equal to seven human years? -- Why do busses often come in threes? -- Why do women talk more than men do, but can't read maps as well as men? -- Why do people need sleep? -- Is the drink Red Bull dangerous? -- Why do people often wake up just before the alarm? -- Do we really use only 10 percent of our brains? -- How do mobile phones work? -- Was the 1959 moon landing a fake? -- When did the game Rock, Paper, Scissors begin? -- Why do people twitch as they fall asleep? -- What is the common cold and how is it cured? -- What is the Internet and how does it differ from the World Wide Web? -- When was toilet paper invented and what was used before then? -- Why do people dream? -- How similar are humans to apes? -- Who wrote the Bible, and when? -- Where does the saying "As mad as a hatter" come from? -- Why do women and not men take birth control pills? -- Why do people have tonsils? -- How intelligent are dolphins? -- How do people count cards in casinos? -- Why do some coins have ridges around the edge? -- Did Robin Hood actually exist? -- Where did the term "rock 'n' roll" come from? -- Why is the professional baseball championship called the World Series? -- How do people pick locks? -- What is the history of the Leaning Tower of Pisa? --, Do hair and fingernails continue to grow after people have died? -- Why do people cry? -- Can babies hear voices while inside the womb? -- Are cats and dogs colorblind? -- How do people speed-read? -- Was Nostradamus able to predict the future? -- What is subliminal advertising and does it work? -- Why does the date for Easter change? -- How do salmon find their exact birthplace? -- What is the origin of the term "rule of thumb" -- Where did the name "Ku Klux Klan" originate? -- How do rabbits and hares differ? -- What is the small thing that hangs at the back of the mouth? -- What is the difference between an ocean and a sea? -- Why is New York City called "the Big Apple"? -- Why do men and women gain weight in different parts of the body? -- What makes a valuable diamond? -- Why do whales beach themselves? -- Why does coffee keep you awake? -- Why do phone numbers in movies all start with 555? -- Why is bellybutton lint generally blue? -- How did the marathon race begin? -- What are aphrodisiacs and do they work? -- Why does human hair turn gray? -- Why does catnip affect cats? -- How do mirrors work? -- Why is Friday the 13th thought to be unlucky? -- How did the word "shit" originate? -- How can you tell if someone is lying? -- Why do men feel sleepy after sex? -- Why do snooze alarms go off every nine minutes? -- Why is "God bless you" said after a sneeze? -- Why can't you tickle yourself? -- Why do bottles of tequila contain worms? -- Why do many prices end in ninety-nine cents? -- What is the difference between AIDS and HIV? -- How can direction be found without a compass? -- Where did the fabric denim originate and why is it stitched with orange thread? -- Why do people have appendixes? -- Why do golf balls have dimples? -- What is the origin of the term "OK"? -- Does an elephant truly never forget? -- Why does sweat smell? -- Why does metal rust? -- Why do we have earwax? -- Why do people shrink with age? --, Why do men have nipples? -- What is acid rain and what causes it? -- What is the purpose of pubic hair and why is it curly? -- Does chewing gum really take seven years to digest? -- Why did Kentucky Fried Chicken change its name to KFC? -- Is drinking too much water bad for you? -- Why are unidentified people called John and Jane Doe? -- What is Coca-Cola made from and did it once contain cocaine? -- How do crocodiles and alligators differ? -- Why did the Romans wear togas? -- Why do we hiccup, and what causes them? -- Why do onions make people cry? -- Can it be too cold to snow? -- Why is getting married called "tying the knot"? -- Why do people stick out their tongues while concentrating? -- How does the Atkins diet work? -- What makes stomachs growl? -- Why do some people sometimes see "stars"? -- Is chocolate addictive? -- Is using a tanning bed bad for your skin? -- How does Viagra work? -- Why is a dollar called a "buck"? -- Where do flies and mosquitoes go in winter? -- Why are people's eyes different colors? -- Does shaved hair grow back thicker and darker? -- What are rainbows and how are they formed? -- Do swimming pools really contain a chemical that reveals urine? -- How did the saying "dressed to the nines" originate? -- Why do people get dizzy if spun around? -- What causes "ringing" in the ears? -- What are the origins of the hamburger and the hot dog? -- What is menstrual synchrony and does it exist? -- Does water pressure plummet during television commercials during the Super Bowl? -- Why do restaurants allow you to taste wine before buying it? -- What is the history of St. Valentine's Day? -- What are computer viruses and how do they work? -- Why does alcohol cause people to urinate so much? -- When was lipstick invented and what was its original purpose? -- Why does the sound of scraping fingernails make people cringe? --, What is the difference between a hurricane and a typhoon? -- How did the word "cocktail" originate for some alcoholic drinks? -- Why is it thought that blonde women have more fun? -- Why is the pirate flag called the "Jolly Roger"? -- Why does the penis shrink when it's cold? -- Is the Caesar salad named after Julius Caesar? -- What is snot and why is it sometimes green? -- How do flies land and walk upside down? -- Why is a rabbit's foot considered good luck? -- Does speaking to plants encourage them to grow? -- What makes people get motion sickness? -- What is the horizon and is the distance to it always the same? -- Why do pregnant women get morning sickness? -- What is the origin of the tattoo? -- What causes people's ears to pop? -- What is the G spot and where is it? -- How do hummingbirds hover? -- What is cancer? -- Why do you never see baby pigeons? -- Why do people get acne? -- How did the "missionary position" get its name? -- Why don't igloos melt on the inside? -- Does wearing tight underwear affect a man's sperm count? -- Where does the expression "pipe dreams" come from? -- Why are parrots the only birds that talk? -- Why do people sneeze? -- Does sitting close to the TV or reading in poor light ruin your eyes? -- How did April Fool's Day originate? -- What is the difference between monkeys and apes? -- How can you tell if someone is flirting with you? -- Why is the number thirteen referred to as a "baker's dozen"? -- When and where did the game of chess originate? -- Why are the terms "bull" and "bear" used in connection with the stock market? -- What are the JFK assassination theories? -- Why does alcohol make people drunk? -- Does penis size vary depending on race? -- What makes animals warm- or cold-blooded? -- Why do pepper shakers have more holes than salt shakers do? -- What is the difference between a donkey, an ass and a mule? -- Is suicide illegal? --, How do microwave ovens cook food? , Is homosexuality a genetic trait? , Did Dracula really exist? , Why do kamikaze pilots wear helmets? , Why do men often shiver after urinating? , What are the Seven Wonders of the Ancient World? , What causes a heart attack? , Why do some beer heads disappear faster than others? , What is hypnosis and is it possible? , Where does the word "hooray" come from? , Why are some men more likely to cheat on their partners than women are? , Do camel humps contain water? , What is gravity and Einstein's theory of relativity? , Why do people crave salt, and why is too much considered bad for you? , Are green potato chips poisonous? , What is the difference between an herb and a spice? , Do taxi drivers have better than average memories? , Can stress cause illness or death? , How can water be found in dry conditions? , Why does the sound of running water give people the urge to urinate? , Where did the term "red herring" originate? , What are the greenhouse effect and global warming? , Why was Stonehenge built? , Why is the Mona Lisa painting so famous? , What are crop circles and what causes them? , Why do people say "Cheers" and clink glasses before drinking? , How can a fire be lit without matches? , What evidence exists about the Loch Ness monster? , What is sea level and does it vary? , What is the best way to immobilize or kill a person using bare hands? , What caused the two World Wars? , Which came first, the chicken or the egg?